PERANAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN OLEH OKNUM APARAT KEPOLISIAN DI POLRES PADANG PARIAMAN - Failin Failin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Law No. 2 of 2002 concerning POLRI is regulated in full and strict regarding the duties and authorities of POLRI, but there are irregularities committed by the POLRI in carrying out its duties. Irregularities committed by POLRI is a violation of the code of ethics that is rarely heard but occurs a lot in POLRI members who are in certain cities that have a dense population. Efforts to enforce the Polri Professional Code of Ethics are needed for the realization of the implementation of the duties charged to the professionalism of POLRI. Unprocompany will greatly impact law enforcement or disclosure of crimes that occur in the community. In the framework of eradicating narcotics syndicates that have so widespread to the Unitary State of the Republic of Indonesia (NKRI), police officers have a very large role and responsibility to maintain the security and stability of the Republic of Indonesia, but facts and reality speak another that it turns out that the police themselves are the perpetrators of criminal acts of the syndicate. There has been a case that happened that the suspect is a police officer. Therefore, it is not surprising that the perpetrators of narcotics abuse crimes are increasing even among the general public but also law enforcement officials, especially the police.Keywords: Role, Police, Countermeasures, Narcotics Crimes